Promoting Students’ Reading Achievement Using Hamburger Strategy - Sartika, Dewi; Pamuji, Arif (English Education Study Program Faculty of Teacher Training and Education, 2021)
This research aimed to promote the reading achievement of the first STIK Bina Husada Palembang midwifery students using the Hamburger strategy. A quasi-experimental method was used, with a non-equivalent group design for the pretest and posttest. The samples consisted of 38 students from STIK Bina Husada Palembang's first-semester midwifery students. A written test with multiple-choice questions was utilized to collect data. The test was found to be both valid and reliable. The value of t-obtained (5.57) was greater than t-table (2.02) at the significant level of p0.05, according to the results of the independent t-test. It was deduced that the Hamburger strategy could promote students’ reading achievement. It meant that the Hamburger strategy could help students improve their reading skills, particularly in recounting text. The Hamburger strategy helped students to stimulate their memory to learn, retain a text, and store information from the text in their long-term memory so that they could remember the information and comprehend the text properly.